Speed Traps and the Right of Silence - Kurzon, Dennis (Research in Language, 2011)
In two English cases which reached the European Court of Human Rights in the mid-2000s, it was argued that the statutory requirement on the part of a motorist who has been caught speeding to give the police information concerning the identity of the driver of the car at the time of the offence is a violation of the right of silence by which a person should not be put into a position that s/he incriminates him/herself. The right of silence is one of the conventional interpretations of Article 6 of the European Convention on Human Rights. As well as a study on the right of silence with regard to written texts, this paper also investigates the two cases in terms of icons and indices: a text may be indexical of a basic human right, and then may become an icon of that right. The European Court of Human Rights considers the particular section of the relevant statute as an icon of the "regulatory regime".